Enhanced corrosion resistance of aluminum 6061 alloy using Ti-based thin films and plasma nitriding - Margono; Djarot B. Darmadi; Femiana Gapsari; Teguh Dwi Widodo; Bayu Mahdi Kartika (JCIS Open)
The corrosion resistance of aluminum alloys is a critical factor limiting their application in aggressive environments, particularly those containing chloride ions. Aluminum 6061, despite its high strength-to-weight ratio, suffers from localized corrosion in such conditions. In this study, Ti, Ti-Ni, and Ti-Ni-N thin films were deposited on aluminum 6061 alloy using the DC sputtering method, followed by plasma nitriding for the Ti-Ni-N film. The results showed that the Ti-Ni film exhibited the best corrosion resistance of 3.64 × 10−4 mm/year, with the lowest icorr of 2.80 × 10−4 A/cm2 and the highest protection efficiency, due to the formation of a stable passive layer. The Ti-Ni-N film also demonstrated enhanced hardness of 392.4 HV, though with slightly higher surface roughness of 5.76 μm. This research contributes to the development of more durable coatings for aluminum alloys, providing improved corrosion resistance in chloride-rich environments.